Overexpression of a Modified Amaranth Protein in Escherichia coli with Minimal Media and Lactose as Inducer - Ismael Morales-Camacho, Jocksan; Dominguez-Dominguez, Jorge; Paredes-Lopez, Octavio (Recent Patents on Biotechnology, 2013)
In this research it was attempted to overexpress the acidic subunit, from the 11S amaranth seed globulin termed amarantin, modified with antihypertensive peptides in Escherichia coli Rosetta (DE3) by manipulating some factors in batch fermenter such as growth medium composition, inducer (isopropyl β-D-thiogalactopyranoside [IPTG] or lactose), air flow, cultivation temperature, agitation speed and induction time. The possibility of using several minimal media and lactose as inducer to increase yields of the recombinant protein was investigated. Previous fermentations at flask level showed that two minimal culture media (A6 and A7) and 0.5% (w/v) lactose presented high yields of the engineered protein expression. Thus, the latter two media were tested at fermenter level, the lactose inducer, and different environmental conditions. Factors with significant effects were identified by Plackett-Burman design with center points and were adjusted at the level suggested and the yields of the recombinant protein were increased from 303.2 to 1,531 mg L-1 in A6 and from 363.4 to 1,681 mg L-1 in A7. Unlike some patents where the highest productivity was achieved at 24 h or afterwards, in this research the best productivity of the recombinant acidic subunit was attained at 4 and 6 h of induction using both media, respectively.
Keywords: lactose